The strategic management process in a border destination: the Eurocity Chaves-Verín - Liberato, Dália (2020)
The aim of this study is to analyse the process of managing a border destination: The Eurocity Chaves-Verín. The research was carried out with a view to different levels of action, namely, to understand the importance of water for the region as a tourist product, to evaluate the positive and negative aspects of the destination development, and to determine the importance of the innovative product “Bio-healthy plans”. Using the qualitative methodology, through semi-structured interviews in a [32] analysis proposal, it was concluded that the model used may be an added value concerning the approach to tourism destinations, because it is considered a wide range model viewing results and plans for future actions, to be implemented at the destination. It is a current model, easily adaptable to the generality of tourism destinations, particularly in the pandemic context of health, experienced in this year. The main results show that we are facing a thermal and wellness destination, which involves all stakeholders, and currently, tourism provides many positive elements for the region.